Results of digital soliton pulse generation and transmission using microring resonators - Sadegh Amiri, I. (Springer Verlag, 2015)
The output signal of single ring resonator for 20,000 round trips of the input signals is simulated. Signals of logic code generated from the single ring resonator can be seen from Fig. 3.1, where the optical power is fixed to 2 W at central wavelength of λ 0 = 1,550 nm and the parameters of the system are selected to n 0 = 3.34, n 2 = 1.4 × 10−13 m2 W−1, Aeff = 0.25 μm2, α = 0.5 dB mm−1, γ = 0.1, R = 10 μm and κ = 0.0225. Figure 3.1a shows the output chaotic signals versus the ring round-trip, where Fig. 3.1b shows the output signals regarding to the input power. The analog and logic codes of the “0” and “1” can be generated and seen from Fig. 3.1c and d. In application, in this research the logic codes of “101010101011010101011101011110101101010101010110101” within the range of 9,050–9,100 round-trip could be generated using chaotic signals from the single ring resonator.